Behavioural and Social Drivers (BeSD) of COVID-19 vaccination for children: A cross-sectional study of parental vaccine confidence and intent in Mysore, India - Kiranmayee Muralidhar; Maiya G. Block Ngaybe; Benjamin Pope; Shivamma Nanjaiah; Kate Coursey; Poornima Jaykrishna; Nagalambika Ningaiah; Todd L. Edwards; Digna R. Velez Edwards; Purnima Madhivanan; Devanshi Somaiya; Karl Krupp (PLoS ONE, 2026)
Background India rolled out COVID-19 vaccinations for adults in January 2021 and children aged 12–18 in early 2022. A 2021 survey indicated that 63% of Indian parents were willing to vaccinate their children against COVID-19, with few studies examining vaccine hesitancy and acceptability. The the Behavioral and Social Drivers of Vaccination (BeSD) framework helps demonstrate which factors may affect vaccination uptake. Our study examined parents’ intentions-to-vaccinate their children below 18 years of age against COVID-19 in Mysore, India and their decision-making process using the BeSD framework. Methods From November 2021 to May 2022, 506 parents/guardians of children below 18 years of age living in Mysore district, India were consented and interviewed by phone or face-to-face. We assessed their own COVID-19 vaccination status, vaccine confidence (Vaccine Confidence Index), intention-to-vaccinate their child against COVID-19, and other factors affecting vaccination such as demographic variables. Multivariable ordinal logistic regression was conducted to examine the association of influencing factors based on the literature and BeSD framework using Stata version 16.1. Intention-to-vaccinate was presented as odds ratios (OR) with associated 95% confidence intervals (95%CI). Results The majority (91.3%) of the 506 participants fully trusted COVID-19 vaccines for their children. The same number (91.3%) had been fully vaccinated themselves, and 78.3% reported being (very) likely to vaccinate their children against COVID-19. Vaccine-hesitant and vaccine-confident groups were not significantly different socio-demographically. As parental age increased, parents had higher odds to express intention-to-vaccinate their child (OR: 1.04, 95%CI: 1.01–1.08). Parents from urban Mysore had lower odds to vaccinate their child compared to those from rural areas (OR: 0.53, 95%CI: 0.35–0.82). Conclusion Most parents expressed vaccine confidence and intention-to-vaccinate their child against COVID-19. Exploring decision-making processes among parents is a crucial strategy to ensure effective implementation of vaccination programs.